Wilhelm Schott als Wegbereiter der deutschen Finnougristik. - Hasselblatt, Cornelius (Finnisch-Ugrische Forschungen, 2014)
The article deals with the German scholar Wilhelm Schott (1802–1889), who is widely known for his Altaic, Chinese and other Asian language studies but whose significance for Uralic studies in Germany is underestimated. The article shows, however, that Schott actually paved the way for Finno-Ugric studies in Germany by conveying the works of August Ahlqvist (1826–1889), Mathias Alexander Castrén (1813–1852), Pál Hunfalvy (1810–1891) and others to a German public. Schott abundantly published on numerous Uralic languages, using mostly two widespread periodicals of the 19th century: the Magazin für die Literatur des Auslandes (1832–1880) and the Archiv für wissenschaftliche Kunde von Russland (1841–1867). In the article, a systematic account of his more than 200 contributions concerning Uralic languages or cultures, forming about a third of his entire production, is given.